" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
f(4) = 0 ===> x = 4 , y = 0
f(4) = 16a + 4b + c = 0
Ingat :
-b/2a = 1
-b/2 = a (1)
subsitusikan (1
-d/4a = 9
-d = 36a
-d = 36(-b/2)
d = 18b
b² - 4ac = 18b
b² - 4(-b/2)(c) = 18b
b² + 2bc = 18b
bagi dengan b
b + 2c = 18
b = 18 - 2c
subsitusikan :
f(x) = ax² + bx + c
f(4) = 0 = 16a + 4b + c
0 = 16(-b/2) + 4b + c
0 = -8b + 4b + c
0 = -4b + c
0 = -4(18 - 2c) + c
0 = -72 + 8c + c
0 = -72 + 9c
9c = 72
c = 8
maka :
b = 18 - 2c
= 18 - 2(8)
= 18 - 16
= 2
maka :
a = -b/2
a = -(2)/2
= -1
f(x) = ax² + bx + c
x = -p
y = p
f(-4) = p = -1(-4)² + 2(-4) + 8
p = -16 - 8 + 8
p = -16